Analisis kepentingan-prestasi dan kepuasan pelanggan terhadap perubahan harga petrol (Analysis of importance-performance and customer satisfaction towards changes in petrol price) - Nora Muda; Safinah Shaharuddin; Noor Aishah Adnan (Penerbit Universiti Kebangsaan Malaysia, 2011)
Basic needs items are one of the biggest expenses in the annual expenditure on household. The increasing of fuel price always be the issue for the increase of the price of basic needs. So, this study were conducted to review the level of importance-performance and satisfaction towards basic needs items price before and after the fuel prices has been increased in Bandar Baru Bangi. The differences in an average expenses of basic needs items have been observed. The methods used in this study are Descriptive Analysis, Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA). The descriptive analysis shows the differences in an average expenditure before and after basic needs price increases. The Customer Satisfaction Index (CSI) is used to measure the customer satisfaction level and found the respondents are less satisfied with basic need prices at the level of 57.58 % after the fuel price increases.Through Importance-Performance Analysis (IPA), there are three attributes that needs to be considered that the increase of basic needs price, withdrawal of subsidies by the government and the net income per month. These attributes should be considered by government to ensure the customer are satisfied with the prices that have been set and also increase the net income per month in line with fuel price increases.